Friction Reduction in Unidirectional Lubricated Sliding Due to Disc Surface Texturing - Slawomir Wos (Coatings, 2020)
Surface texturing is an option of surface engineering resulting in reduction of friction due to the creation of isolated dimples or grooves on sliding surfaces. The purpose of this work is to find the effect of the groove bottom profiles on the reduction of the friction force. Investigations were conducted using an Optimol SRV5 tribotester equipped with a pin-on-disc module. A disc made of 42CrMo4 steel, with a 100 mm diameter acted as a sample. A counter-sample was made of the same material, however, its diameter was 20 mm. The sliding conditions were selected to be similar to those of a sliding crankpin bearing pad operating in a high-performance internal combustion engine. Surface texturing was found to be beneficial for a reduction in the friction coefficient up to 55% in comparison to the untextured disc. Tribological performances of discs with spiral groove patterns were better than those with a radial layout. In most cases the convergent profile of the groove bottom was superior to the dam shape.